Obesity classification in military personnel: a comparison of body fat, waist circumference, and body mass index measurements - Heinrich, Katie M.; Jitnarin, Nattinee; Suminski, Richard R.; Berkel, LaVerne; Hunter, Christine M.; Alvarez, Lisa; Brundige, Antionette R.; Peterson, Alan L.; Foreyt, John P.; Haddock, C. Keith; Poston, Walker S. Carlos (My University, 2012)
Objective: To evaluate obesity classifications from body fat percentage (BF%), body mass index (BMI), and waist circumference (WC). Methods: 451 overweight/obese active duty military personnel completed all three assessments. Results: Most were obese (men=81%; women=98%) using National Institutes of Health (NIH) BF% standards (men>25%; women>30%). Using the higher World Health Organization (WHO) BF>35% standard, 86% of women were obese. BMI (55.5% and 51.4%) and WC (21.4% and 31.9%) obesity rates were substantially lower for men and women, respectively; p<0.05. BMI/WC were accurate discriminators for BF%-obesity (Θ for all comparisons>0.75, p<0.001). Optimal cut-points were lower than NIH/WHO standards; WC=100cm and BMI=29 maximized sensitivity and specificity for men, and WC=79cm and BMI=25.5 (NIH) or WC=83cm and BMI=26 (WHO) maximized sensitivity and specificity for women. Conclusion: Both WC and BMI measures had high rates of false negatives compared to BF%. However, at a population-level, WC/BMI are useful obesity measures, demonstrating fair-to-high discriminatory power.
Keywords: Military personnel; Obesity; Body composition; Body fat percentage; Body mass index; Waist circumference; ROC curves